Tree species coexistence and diversity on elevation gradient of elephant camp natural forest, Nigeria (2022)
Spatial species diversity and size inequality contribute to maintenance of tree species diversity in tropical forests. Coexistence of tree species requires interactions within and between spatial species and size diversity. However, elevation gradient has significant impact on growth and species interactions. Failure of most conservation efforts is due to inability to identify and maintain coexistence mechanisms existing in the forest. Understanding the contribution of elevation gradient to coexistence of tree species will improve conservation efforts and terrestrial carbon budgeting. Therefore, association between tree diversity and size inequality on elevation gradient of Elephant Camp Natural Forest was investigated. Eight (30m x 30m) plots were systematically demarcated on 1km line transects in each identified elevation (Hilltop and Valley-Bottom stands). Trees diameter-at-breast height (dbh) were enumerated and identified to species level. Tree dbh was measured and density estimated. Tree species diversity (Shannon-Weiner, Simpson and Margalef indices) and size inequality (Gini coefficient, skewness and Coefficient of variation) were computed. Stem volume and biomass were computed and converted to biomass carbon. Data collected were analysed using descriptive, correlation analysis and principal component analysis. Tree density varied from 435/ha to 767/ha. There was positive correlation between Skewness and Gini coefficient in Hilltop stand and negative correlation between Skewness and Simpson index in Valley-Bottom stand. The measures of tree size inequality and species diversity were strongly associated with each other in Valley-Bottom stand and not in Hilltop stand. Structural diversity and species diversity determined the competitive interaction among tree communities in Hilltop and Valley-Bottom stands, respectively.